2015
DOI: 10.1016/j.jtcvs.2014.09.121
|View full text |Cite
|
Sign up to set email alerts
|

Directly measuring spinal cord blood flow and spinal cord perfusion pressure via the collateral network: Correlations with changes in systemic blood pressure

Abstract: Spinal cord blood flow is positively correlated with mean systemic blood pressure and spinal cord perfusion pressure under spinal cord ischemia caused by clamping a wide range of segmental arteries. In open and endovascular thoracic and thoracoabdominal surgery, elevating mean systemic blood pressure is a simple and effective means of increasing spinal cord blood flow, and measuring spinal cord perfusion pressure seems to be useful for monitoring perioperative spinal cord blood flow.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
22
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
4
2
1

Relationship

1
6

Authors

Journals

citations
Cited by 28 publications
(22 citation statements)
references
References 29 publications
0
22
0
Order By: Relevance
“…This method estimates SCBF from the rSAP after opening the aortic aneurysm and is based on previously reported results from basic animal research. 9) We clarified the correlations between mean systemic BP, segmental arterial pressure (SAP), and SCBF in the animal study. We found that, even under extensive SA clamping, the spinal cord blood supply via collateral networks remains functional, and SAP is highly and positively correlated with SCBF.…”
Section: Discussionmentioning
confidence: 99%
“…This method estimates SCBF from the rSAP after opening the aortic aneurysm and is based on previously reported results from basic animal research. 9) We clarified the correlations between mean systemic BP, segmental arterial pressure (SAP), and SCBF in the animal study. We found that, even under extensive SA clamping, the spinal cord blood supply via collateral networks remains functional, and SAP is highly and positively correlated with SCBF.…”
Section: Discussionmentioning
confidence: 99%
“…Except for one pair of embolized segmental arteries, operators con rmed no damage to other blood supplies. Besides, blood pressure also plays an important role in blood supply of spinal cord [8], when we think of the issue of low blood pressure (70/40mmHg) did happen after the use of cefuroxime sodium during vertebral prosthesis implantation, which was a delicate moment for spinal cord, because manipulation, low blood pressure and preoperative embolization may together reduce the blood supply to spinal cord. Now therefore, it is highly suspected that on the basis of atherosclerosis, antibiotics or other medicines caused anaphylactic low blood pressure, at the same time, operations may interrupt the circulation of spinal cord, they both together led to thrombosis of anterior spinal artery.…”
Section: Discussionmentioning
confidence: 99%
“…The reasons for that tragedy were carefully discussed in this paper, and a couple of minutes of low blood pressure during operation was deemed to be the main causing factor. While low mean systemic blood pressure was reported to be one of the reasons for cerebral and spinal cord ischemia [8,9], to the best of our knowledge, there are no reports of delayed paraplegia after TES of thoracic metastasis.…”
Section: Introductionmentioning
confidence: 88%
See 1 more Smart Citation
“…High mean arterial pressures (MAP) are also often adopted as a standard practice in the management of acute dissections complicated pre-or postoperatively by spinal cord ischaemia. Despite convincing data supporting this practice [41], it is interesting to highlight that in traumatic spinal cord injuries, no advantages have been demonstrated with arbitrarily set high MAP goals [42], and overall there is limited evidence to support it.…”
Section: A Note On Blood Pressure Management In Acute Aortic Dissectimentioning
confidence: 99%